Comparison between prolozone therapy and extracorporeal shockwave therapy in management of pain and function in resistant cases of lateral epicondylitis: a randomised controlled trial - Chabungbam, Margaret; Singh, Akoijam Joy; Singh, Longjam Nilachandra; Ningthemba, Yumnam; C., Sreejith; Moirangthem, Janet; Pilania, Chandrakant; Opo, Tasso (International Journal of Advances in Medicine, 2020)
Background: Lateral epicondylitis also known as the tennis elbow is a painful condition of the elbow caused by overuse. The disease imparts significant disability to those affected in terms of the quantity and quality of work done. Methods: A randomised controlled trial was conducted in the Department of Physical Medicine and Rehabilitation, RIMS, Imphal for a period of 1 year from February 2017 to January 2018. Eighty-four patients with resistant lateral epicondylitis recruited were divided into 2 groups- group A received Prolozone injection while group B underwent Extracorporeal Shockwave Therapy (ESWT). Results: Assessments of VAS (Visual Analog Scale) and PRTEE (Patient Rated Tennis Elbow Evaluation) were done at 8 weeks and 24 weeks. The mean VAS score in Prolozone group improved from 7.22±0.89 to 4.04±1.01 at 8 weeks to 1.67±0.70 at end of 24 weeks. In ESWT group, mean VAS score improved to 3.91±0.72 at 8 weeks and reduced to 2.3±0.68 at end of 24 weeks. PRTEE improved significantly in both the groups, from 85.33±3.29 to 24.87±2.10 in Prolozone group, and from 85.17±2.83 to 41.89±3.17 in ESWT group. Conclusions: The improvement in pain and disability is better in prolozone group than ESWT (p<0.05) in chronic lateral epicondylitis.